Appraising the e-readiness of online learning facilitators: key human factors - Vermeulen, L. (Koers, 2008)
Higher education institutions in South Africa have undergone a number of changes over the past few years. These changes brought about inter alia changed work environments and job demands. One of the new job demands is the need to incorporate technology in teaching and learning, viz. e-learning. Not all job incumbents, however, adapted successfully to these changes, particularly with regard to e-readiness. Such a lack in e-readiness is likely to influence the effectiveness with which an academic employee will fulfil his/her online learning duties. Therefore, it is important to find solutions to overcome the lack of e-readiness. This article will focus on the role of human resource appraisal, in order to assess the e-readiness of online learning facilitators with a view to improving their online skills and capacity. A number of human factors that can play a role in employee performance and motivation, namely learning styles, personal profile patterns, and pace and style of technology adoption will be briefly outlined, in order to determine the role that these factors could play in assessing the e-readiness of online learning facilitators.